2015
DOI: 10.3758/s13415-015-0393-0
|View full text |Cite
|
Sign up to set email alerts
|

Trying to trust: Brain activity during interpersonal social attitude change

Abstract: Interpersonal trust and distrust are important components of human social interaction. Although several studies have shown that brain function is associated with either trusting or distrusting others, very little is known regarding brain function during the control of social attitudes, including trust and distrust. This study was designed to investigate the neural mechanisms involved when people attempt to control their attitudes of trust or distrust toward another person. We used a novel control-of-attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 78 publications
2
8
0
2
Order By: Relevance
“…The IFG specifically has also been associated with the selection of semantic information (Jefferies, 2013;Wagner, Paré-Blagoev, Clark, & Poldrack, 2001), and it is also involved in the expectation to perform different non-social tasks employing verbal material (e.g., González-García et al, 2017;Sakai and Passingham, 2006). Notably, our results extend this role to a social context (see also Filkowski et al, 2016;Thye et al, 2018;Van Overwalle, 2009), where verbal information is used to generate positive or negative expectations about game partners, by showing that the pattern of activity in this frontal region differs depending on the nature of the information used to predict the proximal behaviour of others.…”
Section: Discussionsupporting
confidence: 72%
“…The IFG specifically has also been associated with the selection of semantic information (Jefferies, 2013;Wagner, Paré-Blagoev, Clark, & Poldrack, 2001), and it is also involved in the expectation to perform different non-social tasks employing verbal material (e.g., González-García et al, 2017;Sakai and Passingham, 2006). Notably, our results extend this role to a social context (see also Filkowski et al, 2016;Thye et al, 2018;Van Overwalle, 2009), where verbal information is used to generate positive or negative expectations about game partners, by showing that the pattern of activity in this frontal region differs depending on the nature of the information used to predict the proximal behaviour of others.…”
Section: Discussionsupporting
confidence: 72%
“…The IFG specifically has been also associated with the selection of semantic information (Wagner et al 2001;Jefferies 2013), and it is also involved in the expectation to perform different non-social tasks employing verbal material (e.g., Sakai and Passingham 2006;González-García et al 2017). Notably, our results extend this role to a social context (see also Van Overwalle 2009;Filkowski et al 2016;Thye et al 2018), where verbal information is used to generate positive or negative expectations about game partners, by showing that the pattern of activity in this frontal region differs depending on the nature of the information used to predict the proximal behaviour of others.…”
Section: Discussionsupporting
confidence: 65%
“…Although a broad array of functions are associated with the VLPFC -language processing (Wagner et al, 2014), mental imagery (Kleider-Offutt et al, 2019), planning (Fincham et al, 2002), selective bias of behaviorally relevant information (Blackwood et al, 2000), and selection among competing information to guide a response (Thompson-Schill et al, 1998) former findings emphasize the role of the VLPFC in cognitive control and inhibition (Bereczkei et al, 2015). For example, a previous study revealed that control of distrust and individual differences in change of distrust are linked with left VLPFC activity, reflecting an increased engagement of cognitive control in individuals who tend to change their distrust evaluations (Filkowski et al, 2016).…”
Section: Discussionmentioning
confidence: 90%